Orthodontic Treatment of an Ankylosed Maxillary Central Incisor through Osteogenic Distraction - DOLANMAZ, DOĞAN; Dolanmaz, DOĞAN; Karaman, Ali Ihya; Pampu, A. Alper; Topkara, Ahu (My University, 2010)
Tooth ankylosis is one of the various problems in dentistry and requires special treatment approaches for satisfactory results. In the orthodontic treatment of an ankylosed tooth, different treatment modalities have been put into practice including both orthodontic and orthodontic-surgical approaches. For favorable results, gingival margin esthetics must be considered as much as leveling the ankylosed tooth in the arch. Distraction osteogenesis accompanied by orthodontic mechanics is a sensible way of achieving this goal. However, devices used in the distraction protocol are high in price and bulky in shape, causing functional and esthetic problems for the patient. This report describes treatment of an infrapositioned ankylosed incisor with continuous distraction forces produced by conventional orthodontic mechanics. In conclusion, the ankylosed tooth was leveled in the upper arch successfully with a harmonic gingival margin. (Angle Orthod 2010; 80:391-395.)